Tumor targeted micellar nanocarriers assembled from epipodophyllotoxin-based amphiphiles. Issue 19 (8th May 2019) - Alliot, Julien; Theodorou, Ioanna; Nguyen, Dinh-Vu; Forier, Cynthia; Ducongé, Frédéric; Gravel, Edmond; Doris, Eric
Abstract : Micelle-forming amphiphilic epipodophyllotoxin conjugates were synthesized and evaluated in vivo for their tumor targeting properties. Abstract : Micelle-forming amphiphilic drug conjugates were synthesized starting from a biologically active epipodophyllotoxin derivative which was covalently inserted in between a hydrophilic PEG unit and a hydrophobic stearyl chain. The epipodophyllotoxin-containing amphiphiles were assembled into the corresponding micelles which were evaluated in vivo for their tumor targeting properties.